Finite element analysis of modified pedicle screw fixation and traditional lumbopelvic fixation for the treatment of sacroiliac joint disruption - Jun Zhang; Yan Wei; Weizhong Yin; Jian Wang; Bingli Liu; Rongguang Ao; Baoqing Yu (BMC Musculoskeletal Disorders)
Abstract Introduction The modified pedicle screw fixation (PSF) was designed to simulate an integrated framework structure to ameliorate the resistance to vertical and shearing forces of the disrupted sacroiliac complex, and the aim of this study was to compare the biomechanical characteristics of PSF and traditional lumbopelvic fixation (LPF) for the treatment of sacroiliac joint disruption. Methods The digital computer simulation model of an intact spine-pelvis-femur complex with main ligaments was built from clinical images. A left sacroiliac joint disruption model was mimicked by removing the concerned ligaments. After model validation, the two fixation models (modified PSF and traditional LPF) were established, and assembled with the disruption model. Under five loading scenarios (compression, flexion, extension, right bending, and left twisting), the finite element simulation was implemented. The maximum von Mises stress (VMS) of internal fixations and pelvises, maximum deformations on the Z-, Y-, X-axes and overall deformation of the sacrum were evaluated and compared. Results Under all loading conditions, the maximum VMS of internal fixations and pelvises in the modified PSF model were lower than those in the traditional LPF model. Under flexion, right bending, and left twisting, the maximum Z-axis deformation of the sacrum for the modified PSF model was smaller than that of the traditional LPF model. For compression, the maximum Y-axis deformation of the sacrum was smaller than that of the traditional LPF model. During various loading modes, the maximum X-axis, and overall deformations of the sacrum for the modified PSF model were smaller than those in the traditional LPF model. Conclusions Compared with the traditional LPF, the modified PSF shows superior biomechanical stability, with satisfied resistance to vertical and shearing forces, which might be potentially suitable for treating sacroiliac joint disruption.